Hydrogen Sulfide Inhibits High-Salt Diet-Induced Myocardial Oxidative Stress and Myocardial Hypertrophy in Dahl Rats - Huang, Pan; Shen, Zhizhou; Yu, Wen; Huang, Yaqian; Tang, Chaoshu; Du, Junbao; Jin, Hongfang (Frontiers in Pharmacology, 2017)
The study aimed to examine the protective effect of hydrogen sulfide (H2S) on high-salt-induced oxidative stress and myocardial hypertrophy in salt-sensitive (Dahl) rats. Thirty male Dahl rats and 40 SD rats were included in the study. They were randomly divided into Dahl control (Dahl + NS), Dahl high salt (Dahl + HS), Dahl + HS + NaHS, SD + NS, SD + HS, SD + HS + NaHS, and SD + HS + hydroxylamine (HA). Rats in Dahl + NS and SD + NS groups were given chow with 0.5% NaCl and 0.9% normal saline intraperitoneally daily. Myocardial structure, α-myosin heavy chain (α-MHC) and β-myosin heavy chain (β-MHC) expressions were determined. Endogenous myocardial H2S pathway and oxidative stress in myocardial tissues were tested. Myocardial H2S pathway was downregulated with myocardial hypertrophy featured by increased heart weight/body weight and cardiomyocytes cross-sectional area, decreased α-MHC and increased β-MHC expressions in Dahl rats with high-salt diet (all P < 0.01), and oxidative stress in myocardial tissues was significantly activated, demonstrated by the increased contents of hydroxyl radical, malondialdehyde and oxidized glutathione and decreased total antioxidant capacity, carbon monoxide, catalase, glutathione, glutathione peroxidase, superoxide dismutase (SOD) activities and decreased SOD1 and SOD2 protein expressions (P < 0.05, P < 0.01). However, H2S reduced myocardial hypertrophy with decreased heart weight/body weight and cardiomyocytes cross-sectional area, increased α-MHC, decreased β-MHC expressions and inhibited oxidative stress in myocardial tissues of Dahl rats with high-salt diet. However, no significant difference was found in H2S pathway, myocardial structure, α-MHC and β-MHC protein and oxidative status in myocardial tissues among SD + NS, SD + HS, and SD + HS + NaHS groups. HA, an inhibitor of cystathionine β-synthase, inhibited myocardial H2S pathway (P < 0.01), and stimulated myocardial hypertrophy and oxidative stress in SD rats with high-salt diet. Hence, H2S inhibited myocardial hypertrophy in high salt-stimulated Dahl rats in association with the enhancement of antioxidant capacity, thereby inhibiting oxidative stress in myocardial tissues.